(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3GdeXaQ Hf YeQ eMeO GdejGaGQbi s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jSJMbg abO GdJeS efi HYV NdU ENhGfi , hef jdRefi ESYGag Cf CUfa ai GdWH cJGHkG eTJedG Ydi bhGfjfg GdcdjI hGdLRFjI GTJeGdG jLeY Edi GdTQM s
(3BNQgG (B:s
(3adjcf gPG GdbOQ ef cdGefG GdeNJUQ ai GdCehQ GdcdjI dUfGYI GdWH cGajkG , hdfCNP ai JUfja cJGHfG ai GdCOhjI GdeaQOI , eSJYjfjf HGddg GdYdi GdcHjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdcJGH GdChds
(3hjTJed Ydi GdCehQ GdcdjI ai Yde GdWHs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs